PROMOSI OBJEK WISATA TAMAN PANORAMA KOTA BUKITTINGGI SUMATERA BARAT - Heru Aulia; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Tourism in Indonesia is an important economic sector, the development of tourism in Indonesia is currently growing rapidly. The development of the tourism sector is promising and provides many benefits to the government, society and the private sector. This is because tourism is a sector that has competence and opportunities to be developed as an asset that is used as a promising source for the government or the community around tourism objects. One of them is West Sumatra Province which is a strategic tourism area where every region has natural beauty which has tourist attractions in every destination that is presented in almost every region in West Sumatra but currently the promotional activities carried out are still not fully running. one-way flow of information or persuasion or made to direct an organization or person to action that creates exchange in marketing by planning and executing a good promotion strategy will also generate revenue and visits. One of the tourist objects in Bukit Tinggi studied is the Bukit Tinggi Panorama Tourism Object which aims to find out how the Bukit Tinggi Panorama Tourism Object is promoted. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and analysis. The Promotion Strategy includes conditional reporting in advertising, sales promotion, public relations and personal selling. Based on the results of the research that has been done, as a whole from the results of observations and interviews, it can be concluded how the Promotion of the Bukit Tinggi Panorama Tourism Object has been carried out although there is still much to be improved. Keywords: Promotion, Attractions